Awareness, knowledge and attitude toward influenza vaccination in several population groups in China: A cross-sectional study - Jiang, Binshan; Wang, Zhenzhong; Jia, Mengmeng; Yan, Huijiao; Su, Zheng; Liu, Shujun; Yang, Weizhong; Qiao, You-lin; Feng, Luzhao (Frontiers in Public Health, 2022)
Abstract Background： We aimed to comprehensively analyze awareness and attitude toward influenza vaccine and the impact factors among the young and middle-aged general population, healthcare workers, and health-related administrators in China. The influencing factors of the promotion of influenza vaccination were also evaluated among healthcare workers and administrators. Methods： This is a multicenter, cross-sectional study. General adults, medical personnel, and health administrators were enrolled in seven regions across China during the 2020-2021 flu season. Data were collected via an online questionnaire, including their awareness, knowledge, and attitude towards influenza vaccination. Results: A total of 3239 individuals were included in our analyses. There were gaps in consciousness to action, especially between awareness (87.1%) and knowledge (57.7%), and between willingness (57.3%) and vaccination (22.3%). The downward trends were similar in all three groups. Medical personnel group and the health administrator group were more aware of influenza vaccines than the general population. For the general group, those with a degree lower than a bachelor's (aOR=0.66) were less likely to be vaccinated. For the medical staff group, practitioners older than 45 years (aOR=0.41) were more reluctant to be vaccinated than those under 25 years. For the health administrator group, personnel aged 26 years and above were less inclined to be vaccinated (aORs=0.17 to 0.20). In all groups, people who had received influenza vaccines in the past 5 years (aOR=1.72, 13.05, and 19.30, respectively) were more likely to be vaccinated in future seasons. People who were not covered by the favorable policies or those without awareness of the related programs were less likely to be vaccinated (aORs<0.63, p-values<0.05). Most (70.8%) of medical staff showed intention to recommend the influenza vaccine. Doctors, those who had flu shots themselves, and those who had more knowledge were more like to make recommendations. Health administrators stated that insufficient capital and workforce, and low public awareness are main difficulties in the promotion of influenza vaccine. Conclusion： The influencing factors of the attitude towards influenza vaccination vary across populations. Governments need to carry out focused vaccination promotion programs, especially for healthcare workers, to improve the coverage of influenza vaccination.